Insegnare la storia italiana in modo semplice e chiaro - Pallotti, Gabriele (Incontri. Rivista europea di studi italiani, 2011)
How to Teach Italian History in a Clear and Simple Way   The article discusses how Italian history can be presented to native and non-native learners in a clear and interesting way. After discussing how and why history textbooks can be obscure, difficult and demotivating, some general principles for writing more effective texts are presented. Examples are drawn from a book on Italian history, Che storia! (G. Pallotti, G. Cavadi, 2011). This book presents a succint account of over twenty centuries in little more than 150 pages. This is achieved by a drastic reduction of references to names, dates, specific events. Rather, special attention is given to aspects of social, economical and political life, which help the reader understand how people lived in a certain time and how some social dynamics are still relevant for understanding today’s world. These aspects of social life are presented in the form of very concrete details about how people lived, what they ate, how they worked. Such details aim at stimulating the reader’s interest, while at the same time illustrate the general character of an epoch. The article also tackles the problematic issue of finding the right balance between clarity and stylistic adequacy, leading to reading pleasure. These two legitimate objectives are sometimes in contrast with each other and authors should be aware of the choices they make and their consequences on a given population of readers.